The validity and reliability of the Turkish version of the Seattle Angina Questionnaire - ŞANAL TOPRAK, CANAN; DURUÖZ, MEHMET TUNCAY (TURKISH SOC CARDIOLOGY, 2020)
Objective: The purpose of this study was to assess the validity and reliability of a Turkish version of the Seattle Angina Questionnaire (SAQ) in patients with coronary heart disease (CHD) and angina. Methods: The SAQ was translated from English to Turkish using the back-translation method. It contains 19 questions scored from 1 to either 5 or 6 in 5 domains (physical limitation, angina stability, angina frequency, disease perception, and treatment satisfaction). Cronbach's alpha coefficient was used to evaluate internal consistency. Spearman's rank correlation coefficient was calculated to assess the construct validity. Convergent validity was examined using correlations between the SAQ and the MacNew Heart Disease Health-related Quality of Life Questionnaire (MacNew) and the Nottingham Health Profile. Divergent validity was evaluated using correlations between the SAQ and age, body mass index (BMI), gender, and the marital status of patients. A value of p<0.05 was considered statistically significant. Results: Sixty-seven patients were enrolled in the study. The mean age of the study patients was 58.7 years (SD: 10.2). Cronbach's alpha scores of the SAQ, ranging in value from 0.715 to 0.910, demonstrated that this scale is reliable. All of the SAQ scales had a significant correlation with all of the MacNew scales, which indicated that the scale has convergent validity. Insignificant correlations with age, BMI, gender, and marital status illustrated the good divergent validity of the scale. Conclusion: The Turkish version of the SAQ is a valid and reliable instrument. It is a useful and practical tool to evaluate patients with angina and CHD.
Keywords: Angina; quality of life; reliability; Seattle Angina Questionnaire; validity; QUALITY-OF-LIFE; STABLE ANGINA; FUNCTIONAL STATUS; PECTORIS; OUTPATIENTS; OUTCOMES